Atmospheres of recovery: Assemblages of health. (January 2016) - Duff, Cameron
This article investigates recovery from mental health problems with reference to recent geographical analysis of affective atmospheres. In so doing, my research responds to recent calls to clarify the ways social, spatial and political factors may promote or impede recovery. As it is normally deployed, the notion of recovery emphasises the deeply personal character of rehabilitation from mental illness. It describes neither the full restoration of health (as a return to some 'pre-morbid' condition), nor the symptomologies characteristic of chronic illness, introducing the need for new ways of conceiving of a kind of health in illness . Throughout my analysis, I will treat recovery as an emergent capacity to manipulate the affects, spaces and events of a body's "becoming well". The always-unfinished event of recovery links human and nonhuman spaces, bodies, objects and forces in the joint expression of an enhanced capacity to affect (and be affected by) other bodies and spaces. I ground this discussion in analysis of ethnographic data collected in studies of recovery conducted in Melbourne, Australia. In presenting my findings, I will focus on three discrete atmospheres encountered in the course of this inquiry, and the ways these atmospheres modulated particular recovery events. In each instance, I will explore how atmospheres were encountered and co-constituted in the work of recovery, in the creation of an assemblage of health, and how these atmospheres gave social and material form to the process of becoming well. I will conclude by assessing how an attunement to affects, spaces and bodies may yield novel means of "staging" atmospheres of recovery in the promotion of an assemblage of health.